THE CORRELATION AMONG SELF CONFIDENCE AND VOCABULARY MASTERY TOWARD SPEAKING ABILITY - setiawan, bambang (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This research aims to answer whether there is simultaneous correlation among students’ self-confidence, vocabulary mastery and students’ speaking ability of the second grade students of MTsN Pare or not. The research used a quantitative method as research design. Quantitative was related to the computation of number. It was taken from answer of questionnaire and test. There were two questionnaires used related to the self confidence and speaking ability and there was one test used related to vocabulary mastery. Each questionnaire contained 20 numbers for self confidence and 20 numbers for speaking ability. The test contains 20 numbers for vocabulary mastery. The result of this research was described based on the data. In this case, the second grade of the second year students’ of MTsN pare were taken as population consisting of 168 as samples taken by Sloven Theory. The data analysis was computed using Statistical Package for Social Sciences (SPSS) version 16,0. The regression table shown the result of self confidence and vocabulary mastery significanly contribute to the speaking ability. By confirming the table regression shown that the value of F table is 12,255 (p<0,05). It means that the data rejects null hypothesis and accept the alternative hypothesis.